The Longitudinal Association Between Competitive Video Game Play and Aggression Among Adolescents and Young Adults. Issue 6 (27th June 2016) - Adachi, Paul J.C.; Willoughby, Teena
Abstract : The longitudinal association between competitive video game play and aggression among young adults and adolescents was examined. Young adults ( N = 1, 132; M age = 19 years) were surveyed annually over 4 years about their video game play and aggression, and data from a 4‐year longitudinal study of adolescents ( N = 1, 492; M age = 13 years) was reanalyzed. The results demonstrated a longitudinal association between competitive video game play and aggressive behavior among both age groups. In addition, competitive video game play predicted higher levels of aggressive affect over time, which, in turn, predicted higher levels of aggressive behavior over time, suggesting that aggressive affect was a mechanism of this link. These findings highlight the importance of investigating competitive elements of video game play that may predict aggression over time.